Synthesis of biologically active substances based on coordination compounds of copper (II) with acetylacetone and salicylic acid - Fatkhullaeva, Muyassar; Gazieva, Aziza Sunnatovna; Viktorovich, Kolesnik Sergey; Akbar ugli, Umarov Ulugbek (International Journal of Psychosocial Rehabilitation, 2020)
There have been studied the synthesis and physic-chemical study of metal acetylacetonates of the composition Ме (acac-Н)2 in some detail. However, there has not been studied the compatibility of this ligand in the coordination sphere of a metal ion with O and N ligands. Present research work is devoted to the synthesis and study of the structure of mixed ligand coordination compounds of copper (II) with acetylacetone (acac) and salicylic acid (SA). There were synthesized the coordination compounds of copper (II) acetylacetonate with salicylic acid. There were studied the elemental composition and some physicochemical properties of the obtained complexes. For establishing the purity and individuality, were obtained radiographs of the starting materials and complexes. X-ray diffraction patterns of Cu (acac-H) 2 and SA sharply differ from the synthesized current complexes, which confirm their individuality and purity. Using the method of IR spectroscopy and derivatographic analysis, it was found that in complex compounds, salicylic acid is invariably coordinated to the metal through the oxygen atom of the carboxyl group, and acetylacetone in different tautomeric forms.